Consumer involvement in the tertiary‐level education of mental health professionals: A systematic review. (16th April 2013) - Happell, Brenda; Byrne, Louise; McAllister, Margaret; Lampshire, Debra; Roper, Cath; Gaskin, Cadeyrn J.; Martin, Graham; Wynaden, Dianne; McKenna, Brian; Lakeman, Richard; Platania‐Phung, Chris; Hamer, Helen
Abstract A systematic review of the published work on consumer involvement in the education of health professionals was undertaken using the PRISMA guidelines. Searches of the CINAHL, MEDLINE, and PsychINFO electronic databases returned 487 records, and 20 met the inclusion criteria. Further papers were obtained through scanning the reference lists of those articles included from the initial published work search (n = 9) and contacting researchers in the field (n = 1). Thirty papers (representing 28 studies) were included in this review. Findings from three studies indicate that consumer involvement in the education of mental health professionals is limited and variable across professions. Evaluations of consumer involvement in 16 courses suggest that students gain insight into consumers' perspectives of: (i) what life is like for people with mental illness; (ii) mental illness itself; (iii) the experiences of admission to, and treatment within, mental health services; and (iv) how these services could be improved. Some students and educators, however, raised numerous concerns about consumer involvement in education (e.g. whether consumers were pursuing their own agendas, whether consumers' views were representative). Evaluations of consumer involvement in education are limited in that their main focus is on the perceptions of students. The findings of this review suggest that public policy expectations regarding consumer involvement in mental health services appear to be slowly affecting the education of mental health professionals. Future research needs to focus on determining the effect of consumer involvement in education on the behaviours and attitudes of students in healthcare environments.